2020
DOI: 10.3390/cells9040840
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor OVOL2 Represses ID2 and Drives Differentiation of Trophoblast Stem Cells and Placental Development in Mice

Abstract: Trophoblasts are the first cell type to be specified during embryogenesis, and they are essential for placental morphogenesis and function. Trophoblast stem (TS) cells are the progenitor cells for all trophoblast lineages; control of TS cell differentiation into distinct trophoblast subtypes is not well understood. Mice lacking the transcription factor OVO-like 2 (OVOL2) fail to produce a functioning placenta, and die around embryonic day 10.5, suggesting that OVOL2 may be critical for trophoblast development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Two kinds of EVTs are reported in the second trimester human placenta: the proliferative EVTs in the cell columns and the invasive endovascular or interstitial EVTs ( Pollheimer et al, 2018 ; Turco and Moffett, 2019 ), and both of these have a unique transcript signature ( Liu et al, 2018 ). Herein, we observed that while the levels of TAC3 and other molecules associated with columnar versus invasive EVTs are not significantly different between ACE2 + TMPRSS2 + and ACE2 – TMPRSS2 – second trimester EVTs, the double-positive cells overexpressed key invasive EVT markers such as OVOL2, GJA5, ICAM and AKT1 ( Sharma et al, 2016 ; Bai et al, 2018 ; Liu et al, 2018 ; Jeyarajah et al, 2020 ), suggesting that these cells are invasive trophoblasts. We further observed that many of the ACE2 + TMPRSS2 + cells were enriched for genes having a role in cell migration.…”
Section: Discussionmentioning
confidence: 78%
“…Two kinds of EVTs are reported in the second trimester human placenta: the proliferative EVTs in the cell columns and the invasive endovascular or interstitial EVTs ( Pollheimer et al, 2018 ; Turco and Moffett, 2019 ), and both of these have a unique transcript signature ( Liu et al, 2018 ). Herein, we observed that while the levels of TAC3 and other molecules associated with columnar versus invasive EVTs are not significantly different between ACE2 + TMPRSS2 + and ACE2 – TMPRSS2 – second trimester EVTs, the double-positive cells overexpressed key invasive EVT markers such as OVOL2, GJA5, ICAM and AKT1 ( Sharma et al, 2016 ; Bai et al, 2018 ; Liu et al, 2018 ; Jeyarajah et al, 2020 ), suggesting that these cells are invasive trophoblasts. We further observed that many of the ACE2 + TMPRSS2 + cells were enriched for genes having a role in cell migration.…”
Section: Discussionmentioning
confidence: 78%
“…Two kinds of EVTs are reported in the second trimester human placenta: the proliferative EVTs in the cell columns and the invasive endovascular or interstitial EVTs (Pollheimer et al, 2018;Turco and Moffett, 2019), and both of these have a unique transcript signature (Liu et al, 2018). Herein, we observed that while the levels of TAC3 and other molecules associated with columnar versus invasive EVTs are not significantly different between ACE2 + TMPRSS2 + and ACE2-TMPRSS2-second trimester EVTs, the double-positive cells overexpressed key invasive EVT markers such as OVOL2, GJA5, ICAM and AKT1 (Sharma et al, 2016;Bai et al, 2018;Liu et al, 2018;Jeyarajah et al, 2020), suggesting that these cells are invasive trophoblasts. We further observed that many of the ACE2 + TMPRSS2 + cells were enriched for genes having a role in cell migration.…”
Section: Discussionmentioning
confidence: 75%
“…OVOL2 deletion inhibits the differentiation of trophoblast stem cells such that they express higher levels of stem cell-related genes such as eomes, esrrb, and id2, and genes involved in differentiation such as gcm1, tpbpa, prl3b1, and syna are downregulated. In addition, ectopic expression of OVOL2 results in the precocious differentiation of trophoblast stem cells [Jeyarajah et al, 2020]. Downregulation of OVOL2 has been implicated in EMT induction upon the implantation of non-invasive bovine trophoblast to the uterine endometrial lining.…”
Section: Trophoblast Developmentmentioning
confidence: 99%